Impact of NGOs on women's empowerment and voice in Bangladesh - Mahzab, Moogdho; Quisumbing, Agnes R.; Kyle, Jordan; Simi, Sonjida Mesket (International Food Policy Research Institute, 2025)
Bangladesh continues to experience persistent gender inequalities shaped by cultural, religious, and social norms. Within its patriarchal social structure, women’s roles are commonly limited to reproductive work or household-based productive activities. These tasks are essential to family well-being but unpaid, undervalued, and routinely overlooked compared to men’s work (Efroymson et al., 2007). These norms have historically constrained women’s visibility, mobility, and participation in the public sphere.